Educational administration in a Philippine Muslim community setting a comparative case study - Maruhom, Melinda C. de Los Santos 1947-
This study investigates the nature and difficulties of public elementary school administration as carried on by two Maranao Muslim principals. It uses the role theory of Getzels that educational administration is a social process involving two dimensions: (1) the institution, with certain rules and expectations that will fulfill the goals of the system; and (2) the individuals, with certain personalities and dispositions inhabiting the system, whose observed interactions comprise social behavior. No conflict was discovered between the institutional and various publics' expectations of a principal's role. These publics (teachers, other principals and head teachers, supervisors, and community members) have similar verbalized expectations with regards to such role although these do not necessarily conform to actual